Reference Values for Waist Circumference and Waist-Height Ratio in Korean Children and Adolescents - Jieun Lee; Sung-Chan Kang; Obin Kwon; Seung-sik Hwang; Jin Soo Moon; Jaehyun Kim (Journal of Obesity & Metabolic Syndrome, 2022)
Background : Abdominal obesity, which is a strong indicator of cardiometabolic risk, is widely evaluated using waist circumference (WC) and waist–height ratio (WHtR). In Korea, the reference values for WC for children and adolescents were published in 2007 and need to be revised. Moreover, there is no reference for WHtR. The aim of this study was to establish new reference values for WC and WHtR in Korean children and adolescents. Methods : Data of 20,033 subjects from the Korea National Health and Nutrition Examination Survey (2007–2019) were used. Tables for reference values and the graphs of smoothed percentile curves of WC and WHtR for children and adolescents aged 2–18 years by sex were generated using the LMS method and locally estimated scatterplot smoothing regression analysis after removing extreme values. Results : Sex-specific reference tables and percentile curves for WC and WHtR were developed. In the new WC curves, the 10th, 50th, and 90th percentile lines were lower than the corresponding lines of the 2007 reference for both sexes. The WHtR curves showed sex-specific differences, although they demonstrated a relative plateau among those aged ≥10 years in both sexes. In the logistic regression analysis, the WC and WHtR z-scores showed higher odds ratios for predicting cardiometabolic risk factors than the body mass index z-score. Conclusion : New WC and WHtR reference values for Korean children and adolescents aged 2–18 years were developed using the latest statistical methods. These references will help monitor and track WC and WHtR for evaluating abdominal obesity among at-risk children and adolescents in Korea.